Pengembangan Digitalisasi Usaha Mikro Kecil Menengah Di Dusun Sawohan Sidoarjo - Mochammad Arkansyah; Wahyu C; Yhola P; Derry Nur; Natasya M (Prapanca : Jurnal Abdimas, 2021)
The government supports Indonesian citizens to run micro, small and medium enterprises, especially in Sidoarjo Regency. They are supported to be able to penetrate the halal market and carry out trade processes in the global market to introduce local products. The problem that occurs is that the training is not evenly distributed in its implementation, for example in Sawohan Hamlet there are several micro, small and medium enterprises such as fish crackers, rengginang, shrimp paste, and udan crackers whose business actors do not understand how to trade in the digitalization era. For example, trading in the digitalization era can use E-Commerce, websites, Instagram business, and others. So that the 2021 Field Work Lecture program can help business actors to better understand technology and be able to sell products easily, because based on the research obtained, business actors currently only get income from selling products to their neighbors.